Analisis Perbandingan Dan Tingkat Akurasi Metode Altman Z-Score, Zmijewski, Springate Dan Grover Dalam Memprediksi Kebangkrutan Perusahaan - Indah Putri Mulya; I Made Murjana; Irianto (Kredibel: Jurnal Ilmiah Manajemen, 2024)
Altman Z-score, Zmijewski, Springate and Grover are company bankruptcy prediction methods. This research aims to determine the comparative results and level of accuracy resulting from each bankcruptcy prediction method, namely the Altman Z-score, Zmijewski, Springate and Grover methods in banking companies State-Owned Enterprises listed on the Indonesia Stock Exchange for the 2017-2022 period. This research is a type of comparative research with a quantitative appproach. The analysis technique uses discriminantanalysis and a level of accuracy test is carried out. The population and sample in this research are 4 State-Owned Enterprise banking companies listed on the Stock Exchage Indoneian Effect. The research sample was determined using the Saturated Sampling method. The results of this study show that the Altman Z-score and Grover methods are the most accurate models with an accuracy rate of 100% and an error rate of 0%. The Zmijewski model foloows later with a low accuracy rate of 12.5% and an error rate of 87.5%. The lowest level of accuracy is owned by the Springate model, namely 0% and an error rate of 100%.